Respon Pertumbuhan Bibit Vanili (Vanilla planifolia) Akibat Pemberian Bokashi Kotoran Ayam - Rafi Juniardi; Yulfi Desi; Yonny Arita Taher (Fakultas Pertanian, Universitas Ekasakti, 2022)
This research has been carried out on Jalan Kandih Raya, Olo Village, Nanggalo District, Padang City, West Sumatra. The research was carried out from January to April 2020. This study aimed to obtain the best Vanilla planifolia (Vanilla planifolia) growth response due to the provision of Chicken Manure Bokashi. The design used was a Randomized Block Design (RAK), with 6 treatments and 4 groups, so that there were 24 trials, in each experiment consisting of 4 plants, the total plants used were 96 plants. As treatment are various doses of Bokashi Chicken Manure, namely: Treatment A = 65 g/seed, B = 75 g/seed, C = 85 g/seed, D = 95 g/seed, E = 105 g/seed, F = 115 g /seedling. The results of the data were analyzed statistically by means of variance (F test). If Fcount > Ftable 5%, then to find out the influential treatments, a further test was carried out with Duncan's New Multiple Range Test (DNMRT). increase, increase in seed length (cm), increase in shoot diameter (mm), increase in the number of leaves (strands), plant fresh weight (g), and plant dry weight (g). Based on the results of the study, it was found that offering several doses of chicken manure bokashi gave different effects on the increase in plant length and weight, but not significantly on the increase in tuna diameter, leaf number, and plant weight. Giving bokashi chicken manure 115 g/seed is the best dose for vanilla seedling growth